Analisis Enkripsi Kriptografi Asimetris Algoritma RSA Berbasis Pemrograman Batch pada Media Flashdisk - Putra, Nathanael Berliano Novanka; Raihana, Fikra Amalia; Mondong, Willem Michael Albert; Kardian, Aqwam Rosadi (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Flashdisk is an external data storage device that is connected to a USB port. Data security is necessary considering that flash drives can be accessed by anyone physically. Therefore, we need a program or application that can act as a secure intermediary for document transfer encryption where users can use flash drives not only to exchange information but also to secure that information. Asymmetric Cryptography is a type of cryptography that utilizes 2 types of keys, namely public keys and private keys. In this study, the RSA Algorithm was chosen to perform encryption because of its better level of security than other asymmetric algorithms, and it can still keep up with technological developments, especially in the security aspect. In this research, an experiment will be carried out to apply asymmetric cryptography using the RSA algorithm in the OpenSSL program to encrypt documents on flash media. The results of the study stated that asymmetric cryptography with the RSA algorithm could perform good encryption on documents contained in flash drives that had used the caraka.bat program.